Indicators and performance requirements for suppliers’ evaluation in the Brazilian electricity sector - Duarte, Thamires Eis; Ribeiro, Priscilla Cristina Cabral; Costa, Helder Gomes (Brazilian Journal of Operations & Production Management, 2024)
Objective: This paper presents a conceptual model comprising performance indicators designed for evaluating suppliers in companies within the electricity sector. Design / Methodology / Approach: The conceptual model was developed based on articles identified from Scopus and Web of Science, which provided indicators and their associated requirements, validated by both academics and practitioners. A multiple case study method was applied, and interviews were conducted with nine participants from six leading companies, which had the highest revenues in the electricity sector in Brazil. The interviews were semistructured and administered remotely. For data analysis, the authors assessed the alignment of the the indicators with the essential requirements for suppliers’ evaluation. This evaluation was carried out using the Lawshe’s (1975) scale, the Content Validity Ratio (CVR), and the critical CVR (Wilson et al., 2012). Results: The conceptual model consists of tree groups of indicators: quality, logistics, and financial. In public companies, the evaluation facilitated external integration, whereas in private companies, this evaluation enabled internal integration. The findings show that some indicators were not applicable to the practice, while all requirements were applicable within the context of both academics and practitioners’ reality. Limitations of the investigation: A notable limitation of this study is the relatively small number of interviewees, particularly within the academic sample. Practical implications: The proposal of these indicators aims to guide companies to a more precise supplier evaluation by procurement and operation departments, which manage a valuable input (spare parts). Originality / Value: The proposal of indicators that meet the requirements, using the Lawshe’s scale and the calculation of the CVR, and further validated by two different actors (academics and practitioners) was not found in the publications concerning suppliers’ evaluation in the electricity sector.